Evaluasi Penerapan Pertolongan Pertama Pada Kecelakaan (P3k) di Pelabuhan Kalimas Surabaya (Menurut Peraturan Menteri Tenaga Kerja dan Transmigrasi Republik Indonesia No. 15 Tahun 2008 Tentang Pertolongan Pertama Pada Kecelakaan di Tempat Kerja) - Kiranti Aisyah Fitri; Muslikha Nourma Rhomadhoni; Merry Sunaryo; Friska Ayu (Jurnal Ilmiah Wahana Pendidikan, 2022)
Potential hazards in the workplace can result in work accidents and occupational diseases. One of the controls against work accidents is the availability of a first aid kit in the workplace. This study aims to evaluate the application of First Aid in Kalimas Port according to Permenakertrans No. 15 of 2008 concerning First Aid in the Workplace. This study used an observational study with a cross sectional. The population in this study were 53 Kalimas Port workers who worked in the warehouse area of ​​PT. Port of Indonesia (Persero) Regional 3 Sub Regional Java. Samples were taken as many as 30 workers with accidental sampling technique. Collecting data using questionnaires and observation sheets based on Permenakertrans No. 15 of 2008. The results showed that 21 workers (70%) did not know the implementation of First Aid in Kalimas Port. The requirements for the first aid officer at Kalimas Port have been in accordance with the regulations set by the Minister of Manpower and Transmigration No. 15 of 2008 which is certified, physically and mentally healthy. The completeness of the first aid facilities, such as the appropriate room, of the 8 first aid boxes available, the contents of all the boxes did not meet the standards; the placement is not clearly visible, 6 of them are located in an inadequate room; 2 boxes are hard to reach; and there is no green first aid symbol yet. There is no means of transportation (ambulance) and shower in additional facilities. The application of First Aid at Kalimas Port was not appropriate, it was found that the box and contents of the First Aid were not in accordance with the standards and workers' knowledge of the application of First Aid was still lacking. Therefore, it is recommended for the company to carry out socialization to workers, improve maintenance and create a logbook for monitoring the first aid kit and contents, adding amap to find out the location of the first aid kit at the Kalimas port.